A comparison of the precipitation behavior in PM γ-γ′ nickel-base superalloys. (28th June 2016) - Semiatin, S. L.; Zhang, F.; Tiley, J. S.; Furrer, D. U.
Abstract : The precipitation of γ ′ in three powder metallurgy nickel-base superalloys during continuous cooling following supersolvus solution treatment was quantified and compared using a fast-acting, mean-field analysis and selected independent experimental observations. The three alloys, LSHR, IN-100 and René 88, were chosen based on the range of γ ′ solvus temperatures and diffusivities which they exhibit. With its intermediate solvus temperature, LSHR served as the baseline material. For all three alloys, the average size of secondary γ ′ (< d s >), which is formed at higher temperatures, followed a dependence on cooling rate of the form < d s > = B −0.5, in which B is a constant whose value increases with solvus temperature. This behaviour was rationalized on the basis of the narrow range of temperature over which nucleation occurs for secondary γ ′, and hence the importance of precipitate growth in controlling precipitate size. The simulation results also revealed that the breadth of the distribution of secondary γ ′ sizes was rather small with the ratio of the standard deviation to < d s > near 0.03 in all cases. In contrast to the behaviour for secondary γ ′, tertiary γ ′ was predicted to nucleate over a broad, but similar, range of temperatures for all of the alloys. Because nucleation and growth of tertiary γ ′ occur at relatively low temperatures, and thus lower effective diffusivities, the sizes of these precipitates were predicted to be more than one order of magnitude smaller than that of the secondary γ ′.